A retrospective cohort study assessing medication coverage in patients with prostate cancer prescribed luteinizing hormone releasing hormone (LHRH) agonists in England. - Ian Sayers; Sara Joao Carvalho; Jennifer Davidson; Naomi Elster; Rakesh Heer; Mohammad Raja; Kate Higgs; Andrew Nolan; Jelena Sassmann (PLoS ONE)
Purpose This study aims to assess adherence to luteinising hormone-releasing hormone (LHRH) agonist treatment for prostate cancer (PC) in England, considering formulation-related differences, their impact on overall survival, and the association with changes in prostate-specific antigen (PSA) levels over time. Methods In this retrospective cohort study, utilising primary care data from the Clinical Practice Research Datalink (CPRD) Aurum database linked to Hospital Episode Statistics (HES) and Office for National Statistics (ONS) death registrations, we assessed male patients aged 40 and above diagnosed with PC and prescribed 1-, 3-, or 6-monthly LHRH agonist injections between January 2007 and December 2019. The primary objectives were to measure adherence through proportion of days covered (PDC) and characterize delayed injections, while secondary objectives included assessment of patient demographics, comorbidities, overall survival, and PSA levels. Descriptive statistics were employed, with follow-up restricted to one year for PSA and testosterone measurements due to data availability constraints. Results The study included 32,777 patients with PC receiving LHRH agonists. Most patients (67%) were prescribed 3-monthly formulations, while only 2% received 6-monthly formulations. The mean age of the study population was 74.1 years. Over 80% of patients had at least one comorbidity, with hypertension being the most common. 94% of patients initially prescribed the 3-monthly or 6-monthly regimen remained on their original treatment, in contrast to only 38% for the 1-monthly formulation. Adherence analysis showed that 41.1% of 6-monthly injections were received without delay, compared with 67.9% for the 3-monthly and 77.3% for 1-monthly formulations. A large proportion of patients experienced delays of 14-27 days (32.0%, 33.4%, 54.2%) and over 27 days (39.6%, 48.3%, 46.6%) across the 1-, 3- and 6-monthly formulations respectively. The mean PDC ranged from 90-91% across the three formulation groups, with 89.9%, 84%, and 88.2% achieving ≥ 80% adherence for 3-monthly, 1-monthly, and 6-monthly respectively. Conclusions This study revealed substantial and consistent dosing delays in LHRH agonist prescriptions across all formulations within primary care settings in England. These delays can negatively affect the control of PC, potentially hindering disease management for affected patients. Future research with a larger population, encompassing a larger cohort using the 6-monthly formulation, is essential for a comprehensive evaluation of the impact of LHRH agonist injection delays on PC progression.